Cultural Formation and Transference Processes of Ancient Greek Theatre - Haluk EMİR; R. Eser KORTANOĞLU (Phaselis: Disiplinlerarası Akdeniz Araştırmaları Dergisi)
Ancient Hellenic theatre, as a central element of the polis life, serves as the focal point of societal actions. The concept of the theatrical, however, is a phenomenon that extends far beyond Hellenic culture, predating the tangible manifestation of theatre by a considerable margin. Although the collective consciousness and ritual practices observed in the Paleolithic, Neolithic and Bronze Ages predate the emergence of Hellenic thought, they played a crucial role in the birth of theatre as a mental concept. The symbolic imagery, and ritual practices encountered in the Paleolithic, Neolithic, and Bronze Ages, although predating Hellenic thought and the emergence of tragedy, serve a determinative function in the genesis of theatre as a mental concept. This interdisciplinary research aims to analyze the roots and developmental stages of ancient Hellenic theatre on a broad scale, without limiting it to the geography of Hellas. The study takes an approach that covers the early cognitive evolution and socio-cultural structuring of humanity. This will enable an understanding of the position of ancient Hellenic theatre within the broader context of human experience.